Effect of Maggot‒Tofu Dreg Mixed Flours with Addition of Lysine on Formulation of Fish Feed to Accelerate the Growth of Tilapia (Oreochromis niloticus) - Akbar Rahmatullah; Vita Paramita; Daffa Ikhlasul Amal; Hermawan Dwi Ariyanto (Universitas Gadjah Mada, 2023)
Maggot flour, which contains high protein has potential in the development of fish feed. The focus of this study was to investigate the formulation of fish feed based on mixed flours (maggot and tofu dregs flours) with the addition of lysine to improve feed quality and feeding efficiency. The Pearson Square Method (PSM) was used in the formulation process of fish feed with a total protein target of 35%. The formulated fish feed was applied on tilapia fish (Oreochromis niloticus). The fish weight and ammonia levels in the water were also measured to determine the effect of fish feed on water quality. The highest protein content (33%) was obtained from ratio of mixed flours of 3:1 (%(w/w)). The highest floatability value of fish feed was 194±2 sec. The optimum results for fish growth were obtained from mixed ratio of maggot flour and tofu dregs of 3:1 % (w/w). with the addition of 2 % (w/w) of lysine. The optimal growth rate of fish was 0.041 g·day-1 after 30 days of the experiment. While the level of ammonia in the water was not affected by the fish feed formulation or the addition of lysine in the fish feed. Thus, the amino acid lysine greatly influences the feed conversion ratio and specific growth rate so that it has the potential to accelerate the growth of tilapia.